Answer:
2. x=-2 y= 2
3. x=3 y=0
Explanation:
-2x - 3 y = -2
y = 2x + 6
The first step is to get x and y on the same side
Take the second equation and subtract 2x from each side
-2x+ y = 2x-2x + 6
-2x+y = 6
Multiply this by -1
-1(-2x+y) =-1*6
2x -y =-6
Add this to the first equation to eliminate x
-2x - 3 y = -2
2x -y =-6
--------------------
-4y = -8
Divide by -4
-4y/-4 = -8/-4
y =2
Now we need to find x
y = 2x + 6
Substituting in y=2
2 = 2x+6
Subtract 6 from each side
2-6 = 2x+6-6
-4 = 2x
Divide by 2
-4/2 = 2x/2
-2 =x
3) -x - 18 y = -3
7x - 9 y = 21
We will eliminate by by multiplying the second equation by -2
-2(7x - 9 y) = -2*21
-14x + 18y = -42
Now we will add this to the first equation
-x - 18 y = -3
-14x + 18y = -42
-------------------------
-15x = -45
Divide by -15
-15x/-15 = -45/-15
x =3
We still need to solve for y
-x -18y = -3
Substituting in x =3
-3 -18y = -3
Add 3 to each side
-3+3 -18y =-3+3
-18y =0
Divide by -18
y= 0